2022
DOI: 10.1111/dom.14730
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy is associated with dysglycaemia: Cross‐sectional and prospective analyses

Abstract: Cholecystectomy has been reported to be associated with increased risk of diabetes in cross-sectional studies. In the current study, we performed both cross-sectional and prospective analyses to examine the association between cholecystectomy and dysglycaemia in Chinese community-dwelling adults. A total of 1612 participants (n = 1564 without cholecystectomy and n = 48 with cholecystectomy) were evaluated for glycaemic status (according to the World Health Organization (WHO) 1999 criteria) and then followed up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Besides facilitating digestion and absorption of nutrients in the intestinal tract, bile acids have recently been recognised as signalling molecules, among others, involved in glucose homeostasis 34,35 . Indeed, cholecystectomy has been associated with increased risk of dysglycaemia, 36 and intrahepatic cholestasis of pregnancy has been associated with impaired glucose tolerance 37 and gestational diabetes 38 . The signalling pathways are diverse and include (i) bile acid‐induced stimulation of intestinal glucagon‐like‐peptide 1 (GLP‐1) secretion through activation of Takeda G protein‐coupled receptor 5 (TGR5) in the enteroendocrine L‐cells 39,40 thus enhancing glucose‐dependent stimulation of insulin and suppression of glucagon 41 and (ii) induction of fibroblast growth factor 19 (FGF‐19) transcription through activation of the nuclear farnesoid X receptor (FXR) in the enterocyte 34 thus inhibiting hepatic gluconeogenesis, 42 stimulating hepatic glycogen synthesis 43 and increasing peripheral glucose disposal in an insulin‐independent manner 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides facilitating digestion and absorption of nutrients in the intestinal tract, bile acids have recently been recognised as signalling molecules, among others, involved in glucose homeostasis 34,35 . Indeed, cholecystectomy has been associated with increased risk of dysglycaemia, 36 and intrahepatic cholestasis of pregnancy has been associated with impaired glucose tolerance 37 and gestational diabetes 38 . The signalling pathways are diverse and include (i) bile acid‐induced stimulation of intestinal glucagon‐like‐peptide 1 (GLP‐1) secretion through activation of Takeda G protein‐coupled receptor 5 (TGR5) in the enteroendocrine L‐cells 39,40 thus enhancing glucose‐dependent stimulation of insulin and suppression of glucagon 41 and (ii) induction of fibroblast growth factor 19 (FGF‐19) transcription through activation of the nuclear farnesoid X receptor (FXR) in the enterocyte 34 thus inhibiting hepatic gluconeogenesis, 42 stimulating hepatic glycogen synthesis 43 and increasing peripheral glucose disposal in an insulin‐independent manner 44 …”
Section: Discussionmentioning
confidence: 99%
“…with increased risk of dysglycaemia, 36 and intrahepatic cholestasis of pregnancy has been associated with impaired glucose tolerance 37 and gestational diabetes. 38 The signalling pathways are diverse and include (i) bile acid-induced stimulation of intestinal glucagon-like-peptide 1 (GLP-1) secretion through activation of Takeda G protein-coupled receptor 5 (TGR5) in the enteroendocrine L-cells 39,40 43 and increasing peripheral glucose disposal in an insulin-independent manner.…”
Section: F I G U R Ementioning
confidence: 99%
“…This study provides support for hypothesis that hormonal alterations caused by cholecystectomy have an impact on the diagnosis and pharmacological treatment of patients with PBH. It is known that BA, through the activation of FXR and TGR5, stimulate the production of GLP-1, an insulinotropic hormone, and hence induce changes in glucose metabolism [ 12 , 18 , 21 ]. Alterations in the kinetics of the BA enterohepatic cycle play a role in the development of PBH [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that BAs play an important role in regulating postprandial glucose metabolism [ 16 ]. Another study discovered that the risk of abnormal blood glucose in individuals undergoing cholecystectomy in Chinese community residents was increased, indicating that BAs is important in maintaining blood glucose [ 17 ]. More studies have also revealed that the role of BAs in blood glucose regulation may be to activate BAs receptors involved in downstream physiological functions [ 18 ].…”
Section: Discussionmentioning
confidence: 99%